Redescription of Tipula octomaculata Savchenko, with notes on related Holarctic species (Diptera, Tipulidae) - Salmela, Jukka; Autio, Olli (Zootaxa, 2007)
Tipula (Pterelachisus) octomaculata Savchenko, 1964 (Diptera, Tipulidae) has hitherto been known only from the type locality in north-western Russia, and no material besides the holotype male has been available for study. In this article we report T. octomaculata for the first time from Finland, redescribe the species and compare its morphological characters with those of related Nearctic species (T. trivittata Say, T. angulata Loew, T. entomophthorae Alexander). The Finnish finding locality in Ks: Taivalkoski, North boreal ecoregion, is briefly discussed.